Gait symmetry measures: A review of current and prospective methods. (April 2018) - Viteckova, Slavka; Kutilek, Patrik; Svoboda, Zdenek; Krupicka, Radim; Kauler, Jan; Szabo, Zoltan
Highlights: Normative data for physiological gait asymmetry is currently missing. Useful recommendations for particular acquisition devices should be given. A substantial portion of measured data is not employed in symmetry analysis. A new subgroup of symmetry measures has emerged — complete gait cycle measures. The definition of gait symmetry should be reconsidered. Abstract: Gait symmetry is important in measuring gait pattern alterations for establishing the level of functional limitation due to pathology, observing its changes over time and evaluating rehabilitative intervention effects. The aim of this topical review is twofold: 1) to present used symmetry measures and summarize their application to a diverse range of gait data and to demonstrate their capabilities in their utilization in research and practice, 2) to expose newly developed symmetry measures and highlight their perspectives. We divided symmetry measures into four subgroups: symmetry indices, complete gait cycle symmetry measures, statistically-based measures and approaches, and nonlinear measures. For each, we will discuss their advantages and limitations and raise new questions and recommendations about their development and clinical use.